Blysmasphaera broennimanni : a new recent allogromiine species (order Foraminiferida, Eichwald, 1830) from Brazil. - Semensatto, Decio Luis; de Oliveira, Denise; Dias-Brito, Dimas (My University, 2008)
Blysmasphaera broennimanni, a new recent allogromiine species from Brazil, is here introduced. This species was mainly found in freshwater and acidic sediments (pH ranged from 4.4 to 5.8). This new species differs from Blysmasphaera brasiliensis Broennimann, 1988 in its wall's outer layer, which is characterized by thin "plates" with everted borders that give the surface an overall net-like appearance. An emendation to the genus Blysmasphaera Broennimann, 1988 incorporating this new observed feature is also proposed.